Tragacanth gum-based hydrogels for drug delivery and tissue engineering applications - Abdi, Gholamreza; Jain, Mukul; Patil, Nil; Tariq, Mohd.; Choudhary, Shipra; Kumar, Pankaj; Raj, Neeraja S.; Mohsen Ali, Saif Saleh; Uthappa, U. T. (Frontiers in Materials, 2024)
Natural polymers have many uses, and Tragacanth gum is just one of them. Many people are interested in natural gums because of their many attractive characteristics, such as being ‘green’ bio-based renewable materials, being easily accessible, inexpensive, and structurally diverse. One class of naturally occurring polysaccharides is called gum because of its tendency to create a gel or a thick solution. Among the many plant-based raw materials, these polysaccharide gums are abundant. Hydrogels, which are three-dimensional polymeric webs that can imitate live tissues, have demonstrated remarkable potential as adjustable biomaterials in numerous regenerative techniques due to their high water or biological exudate absorption capacities. Natural polysaccharides, often known as gums, are present in many different types of trees and possess many desirable properties, such as being renewable, biocompatible, biodegradable, non-toxic, and amenable to chemical modification. Many people are curious about certain parts of the food, water, energy, biotech, environmental, and healthcare sectors as of now. Gum, a type of very important and unique food ingredient, has many vital uses in the food business. Cosmetics, coating, photosensitive resin, fertilizer, casting, pharmaceuticals, and tobacco are just a few of the non-food businesses that make use of their strong water-affinity and structural plasticity. There are a lot of benefits to hydrogels made from natural gums as opposed to those made from synthetic sources. Synthesis hydrogel polymers have been the center of interest among these non-food applications because of their extensive use in the pharmaceutical and medical fields. The Tragacanth gum hydrogels used for medication delivery and tissue engineering have been the focus of this study. We also paid close attention to drug delivery, physical-chemical properties, and the extraction of Tragacanth gum. Our research has a wide range of biomedical applications, including tissue engineering for bone, skin, fixation of bone, periodontal, and cartilage. Possible futures based on hydrogels made of Tragacanth gum were likewise our primary focus.